Pengaruh Parameter Proses Thermoforming Terhadap Distribusi Ketebalan dan Akurasi Dimensi Produk - Budiyantoro, Cahyo; Kurniawan, Perwita (Universitas Muhammadiyah Yogyakarta, 2023)
This study examines the influence of thermoforming process parameters, namely heating time, pre-stretching degree, and vacuum evacuation rate, on the distribution of wall thickness and dimensional accuracy of the product. The research involved a series of experiments with three variations of these process parameters. Heating time was varied at 30, 35, and 40 seconds, pre-stretching degree ranged from 0.1 to 0.3, and evacuation rates were set at 6 mm/s, 8 mm/s, and 10 mm/s, respectively. The results showed that the parameters capable of minimizing the radius at the specimen's corners were a vacuum evacuation rate of 10 mm/s, a heating time of 40 seconds, and a pre-stretching degree of 0.1 Vst. The findings suggest that the vacuum forming products can be optimized by combining a high vacuum evacuation rate, longer heating time, and low pre-stretching degree.